Effects of COVID-19 Pandemic on Working Conditions of Dentists in Poland and Turkey - Sarkis Sozkes; Iwona Olszewska-Czyż (Medicina, 2021)
Background and Objectives: Due to the specific working conditions dental professionals represent a group of high risk of infection and COVID-19 pandemic in many ways have influenced their working environment. The aim of this study was to evaluate effects of COVID-19 pandemic on working conditions of dentists in Poland and Turkey. Materials and Methods: The study was an anonymous online questionnaire conducted among thedentists in two countries: Poland and Turkey. The survey consisted of general questions, COVID-19 pandemic infection and working history as well as working conditions before and during pandemic. Chi-square test, Fisher’s Exact test, Fisher Freeman Halton test and Continuity (Yates) Correction were used to compare qualitative data. Results: The study was conducted with a total of 400 participants, 162 (40.5%) men and 238 (59.5%) women, aged between 23 and 67. The mean age of the participants was 42.39 ± 9.99 years. Positive COVID-19 test results among dentists in Poland were found to be significantly higher than in Turkey. Time of dental procedures during the COVID-19 pandemic in Poland and Turkey was significantly increased. The usage of N95/FFP2 or N99/FFP3 masks and surgical gowns during COVID-19 pandemic compared to pre-COVID-19 periods was clearly higher (p < 0.05). Reusable full-face and half-face elastomeric respirators are increasingly used in Turkey. During the COVID-19 pandemic a 25% decrease in dentists’ income in Poland (81%) was significantly high than in Turkey (47.5%). Conclusions: COVID-19 pandemic has influenced working conditions of dentists. Many dentists got infected during the pandemic, dental procedures’ time has increased, and protective equipment usage has become higher. Further studies analyzing the working conditions of dentists during COVID-19 pandemic should be conducted for better planning of future decisions taken by governments and authorities.